APLIKASI PENJADWALAN UJIAN SKRIPSI DAN KERJA PRAKTEK - Ilham Wahit Ambo; Lillyan Hadjaratie; Roviana H. Dai (Diffusion: Journal of Systems and Information Technology, 2021)
This research is conducted due to the constraints that are often found in organizing the thesis defense and practical work schedules at the departement of informatics Engineering, Faculty of Engineering, State University of Gorontalo. The constraints are in the form of frequent delays in scheduling because the admin has to check the room beforehand, the lecturers' absence, and the time to prevent conflicts in scheduling the research method is a prototype. The research result is an application in scheduling the thesis defense and practical work, which will help organize the thesis defense and practical work schedules in addition, the admin is also able to easilydetermine both schedules in the Departement of Informatics Engineering, Faculty of Engineering, State University of Gorontalo.Keywords: Scheduling Application, Thesis, practical work